The cricketing shoulder: biomechanics and analysis of potential injury risk factors to the shoulder in elite cricketers - Dutton, Megan Charmaine (Department of Human Biology, 2020)
Historically, cricketing literature has explored the disciplines of bowling and batting, with fielding receiving little attention until its importance was highlighted by the introduction of T20 matches. The novelty of this research lies in its clinically meaningful contribution to understanding shoulder injury aetiology in cricketers as overhead throwing athletes. The studies included in this thesis investigate the musculoskeletal profile of a cricketer’s shoulder, as well as the intrinsic factors associated with shoulder injury risk. Further, the influence of some of these risk factors on the cricketers’ overhead throwing biomechanics is explored and intend to improve the development of cricket-specific shoulder injury prevention programmes. An overview of the literature (Chapter 2) includes the epidemiology of shoulder injuries in cricketers; as well as a description of overhead throwing kinematics and the musculoskeletal adaptations associated with overhead throwing in cricket, compared to baseball, which has the greatest volume of throwing related studies. Based on previous outdated definitions of injury and not the current consensus definitions, shoulder injuries in cricket have been reported to occur infrequently. Various injury surveillance studies have identified time-loss shoulder injuries in cricketers, yet none have considered non-time-loss shoulder injuries. Although a limited number of studies have proposed potential intrinsic risk factors to shoulder injury in cricketers, no associations have been found. However, the cricketer’s shoulder is prone to injury due to the high forces generated while repeatedly throwing overhead during fielding. While overhead throwing biomechanics has been well investigated in baseball, minimal research exists for cricket. In addition, the understanding of throwing biomechanics in cricket has relied on two-dimensional motion analysis that is known to be insufficient for the analysis of rotational kinematics and kinetics. Elite (senior national and franchise) cricketers were recruited for this study. This study consisted of two parts. During the first part of the thesis demographic, training, competition and injury history data were obtained; and a shoulder-specific functional questionnaire and pre-season shoulder screening protocol were performed, prior to annual musculoskeletal screening. The incidence of all shoulder injuries were recorded throughout a six month cricket season. A profile of pertinent risk factors was assessed. The second part of the thesis evaluated throwing biomechanics of cricketers. Upper quarter, spinal, pelvic and hip kinematics, as well as shoulder and elbow kinetics were measured during the execution of overhead throwing from a stationary position, and with a run-up. This thesis includes three original papers and two experimental Chapters. The first paper (Chapter 3) documents the incidence of non-time-loss shoulder injuries in elite South African cricketers. Overall, the incidence of shoulder injury in cricketers during the 2016/2017 season was 18%, described as 5% time-loss and 13% non-time-loss injuries. Primary skill and fielding were negatively impacted in 100% and 80% of cricketers who sustained non-time-loss shoulder injuries, respectively. The entire cricket cohort recorded low scores on the shoulderspecific questionnaire, completed pre- and post-season, irrespective of injury history or injury sustained during the 2016/2017 season indicating a generalised reduction in the level of function in overhead activity. Paper 2 (Chapter 4) provides a description of the musculoskeletal profile of a cricketer’s shoulder which is atypical to the “thrower’s paradox” described in baseball. Specifically, cricketers present with a loss in total glenohumeral (GH) rotational range of motion (ROM), GH internal rotation deficit (GIRD) in the absence of external rotation gain (ERG); and global weakness of the rotator cuff and scapula stabilising muscles. Further, dominant shoulder supraspinatus tendon (SsT) thickness ≥5.85mm (sensitivity: 72%, specificity: 63%) and nondominant pectoralis minor length (PML) ≤12.85cm (sensitivity: 83%, specificity: 55%) predicted seasonal dominant shoulder injury (p< 0.05). From the findings indicated in Papers 1 and 2 (Chapters 3 and 4) it can be postulated that cricketers are generally a high-risk population for shoulder injury, amongst overhead throwing athletes, due to the lack of shoulder-specific musculoskeletal adaptation frequently observed in other overhead throwing populations. Paper 3 (Chapter 5) and experimental Chapters 6 and 7 investigate the kinematics and kinetics of overhead throwing from a stationary position, with a run-up and the consequence of GIRD in these two throwing approaches. A kinematic description of overhead throwing in cricket is provided and compared to baseball overhead pitching, in Paper 3 (Chapter 5). Maximum external rotation (MER) was regarded as the most critical point for potential shoulder injury in cricketers when throwing overhead from a stationary position. Further, a comparison between playing levels highlighted that amateur cricketers may display an increased risk for shoulder injury at MER as these cricketers were found to have decreased elbow flexion ROM in 2-14% of the throwing cycle (p=0.01), as well as greater shoulder (p=0.021) and elbow (p=0.043) compression and increased superior shoulder force (p=0.022) at MER, when compared to elite cricketers. Findings from experimental Chapter 6 indicate that when throwing with a run-up (dynamic) increased lumbo-pelvic (p=0.02) and hip flexion (p=0.01) occur sporadically in the throwing cycle, compared to throwing from a stationary position (static). In addition, increased shoulder compression (p=0.02) and posterior force (p=0.009) occur at MER, while reduced superior shoulder force (p=0.005) and elbow compression (p=0.03), superior (p=0.002) and medial (p=0.03) forces occur at ball release (BR), when throwing dynamically versus statically. These two Chapters highlight MER as the most critical point for potential shoulder injury in cricketers, which may further be attenuated by the absence of ERG, level of play and throwing from a stationary position while fielding. Experimental Chapter 7 investigated and highlights the potential correlations between GIRD, a frequently described risk factor for overhead athletes, and the other musculoskeletal variables measured, as well as overhead throwing biomechanics from a stationary and runup approach. Greater GIRD was associated with reduced passive hip external rotation ROM on the dominant side (p< 0.03), measured by inclinometer. In addition, increased GIRD was associated with reduced dominant hip abduction ROM during 0-23% of the throwing cycle (p=0.002), and superior shoulder force (p< 0.004) and elbow compression (p< 0.009), when throwing from a stationary position. Finally, greater GIRD was associated with increased posterior shoulder force at maximum internal rotation (MIR), when throwing from a stationary position (p< 0.013) and with a run-up (p< 0.03). These findings suggest that GIRD may negatively influence ball velocity specifically when cricketers attempt to throw overhead from a stationary position. Further, it is postulated that when throwing overhead (irrespective of approach) cricketers may overcome the mechanical insufficiency of GIRD by actively engaging the dominant hip internal rotators, to prematurely rotate the pelvis forward, in order to generate sufficient ball velocity. This may result in cricketers employing a throw across the body, which when repeatedly performed may cause hypertrophy of the dominant hip internal rotators, thereby reducing passive hip external rotation ROM. This biomechanical adaptation to GIRD may contribute to the cricketer’s predisposition for shoulder injury when throwing overhead, or may occur in an attempt to protect the shoulder against further injury. In conclusion, the inherent musculoskeletal profile of this elite cricketing cohort’s shoulder increases injury risk, particularly when throwing overhead. There is a need to investigate the influence of throwing volume, duration of season and player speciality on the musculoskeletal profile of the shoulder and concomitant injury in cricket. It is suggested that modifiable intrinsic factors found to be associated with shoulder injury and the performance of overhead throwing should be appropriately incorporated into injury prevention or pre-season conditioning programmes, to reduce the occurrence of injury. Further research should determine the efficacy of these programmes on shoulder injury prevention and throwing performance, in cricketers.